2000
DOI: 10.1038/75406
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived green fluorescent proteins for quantifying ubiquitin/proteasome-dependent proteolysis in living cells

Abstract: The ubiquitin/proteasome-dependent proteolytic pathway is an attractive target for therapeutics because of its critical involvement in cell cycle progression and antigen presentation. However, dissection of the pathway and development of modulators are hampered by the complexity of the system and the lack of easily detectable authentic substrates. We have developed a convenient reporter system by producing N-end rule and ubiquitin fusion degradation (UFD)-targeted green fluorescent proteins that allow quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
550
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(585 citation statements)
references
References 28 publications
22
550
0
1
Order By: Relevance
“…S9). Consistent with the inhibitory role of PCA on the autophagic flux, ectopically expressed Arg-HSPA5-GFP, generated from Ub-Arg-HSPA5-GFP, 46 was also significantly stabilized after PCA treatment, along with endogenous Arg-HSPA5, when examined with antiArg-HSPA5-specific antibodies 34 (Fig. 3C).…”
Section: Measurements Of Transiently Overexpressed Gfp-lc3supporting
confidence: 49%
See 1 more Smart Citation
“…S9). Consistent with the inhibitory role of PCA on the autophagic flux, ectopically expressed Arg-HSPA5-GFP, generated from Ub-Arg-HSPA5-GFP, 46 was also significantly stabilized after PCA treatment, along with endogenous Arg-HSPA5, when examined with antiArg-HSPA5-specific antibodies 34 (Fig. 3C).…”
Section: Measurements Of Transiently Overexpressed Gfp-lc3supporting
confidence: 49%
“…For example, Arg-GFP-which is generated from Ub-Arg-GFP fusion proteins 46 after translational cleavage of the Ub-Arg junction by deubiquitinating enzymes and therefore not a substrate of ATE1-was short-lived in WT and ate1 ¡/¡ MEFs but stable in ubr1 ¡/¡ ubr2 ¡/¡ MEFs, under normal conditions ( Fig. 2E to 2G).…”
Section: Measurements Of Transiently Overexpressed Gfp-lc3mentioning
confidence: 99%
“…2B, lane GFP-3a-FRAA). As it has been shown that GFP is not a substrate for ubiquitin-proteasome-dependent proteolysis (Dantuma et al 2000), the target for polyubiquitination was likely the eRF3a moiety of GFP3a-FRAA. Of course, we cannot rule out the possibility that eRF3a forms containing mutations in the eRF1-binding site were misfolded and targeted to ubiquitin-proteasomedependent proteolysis.…”
Section: Resultsmentioning
confidence: 99%
“…A Ubi-GFP was previously used to quantify ubiquitinproteasome-dependent proteolysis in living cells (Dantuma et al, 2000). For this purpose, the DNA fragment from the pDG268 plasmid (kindly provided by Dr D Gray, University of Ottawa, Ottawa, Ontario, Canada), encoding an ubiquitin-EGFP fusion protein (Tsirigotis et al, 2001), was transferred into the pCDNA3 expression vector (Invitrogen Life Science, Carlsbad, CA, USA).…”
Section: Plasmid Constructs and Transfectionmentioning
confidence: 99%